From Unsustainability to MSC Certification: A Case Study of the Artisanal Chilean South Pacific Hake Fishery. Issue 3 (2nd July 2016) - Plotnek, Emma; Paredes, Felipe; Galvez, Mauricio; Pérez-Ramírez, Mónica
ABSTRACT: The Marine Stewardship Council (MSC) certification is a market-based incentive program that recognizes sustainable fisheries through a third-party assessment. This study considers a potential project to MSC-certify the small-scale sector of the South Pacific hake ( Merluccius gayi gayi ) fishery in Chile. Using semi-structured interviews with fishery stakeholders and bibliographic review, the study surveys the technical, stakeholder, and market barriers to certification. Barriers included an over-exploited stock, lack of information about the ecosystem, and the currently-evolving management system. In addition, noncompliance of existing norms and social arrangements within the fishery are leading to a situation where illegal fishing occurs. Even though MSC certification is positively perceived by most stakeholders, it is considered to be neither achievable by the status of the fishery nor desirable, since it cannot offer economic benefits due to the domestic market features. At present, the most constructive actions for the fishery would be to implement strong management and effective enforcement, and break-down the currently unregulated market structure, as well as empower the fishermen. Long-term efforts in these areas may be executed using the MSC Standard as a diagnostic tool to identify the improvements required to move the fishery toward better performance.